Non-Usury Banking Fits the Change Strategy: The Solution to Revive the Economy - Bidabad, Bijan (American Economic & Social Review, 2019)
Based on the working in different fields of sciences for a long time, a solution to change the structure of banking products as a solution to economic crises is proposed. By sharing the risks economically this solution can make economic integrity among all economic sectors.In this paper, we are going to introduce a new Islamic financial institution with elaborated economic and financial characteristics. «Non-Usury Bank Corporation» (NUBankCo) is defined in a way that depositors are the shareholders of the Bank. This corporation is a new kind of shared ownership corporation, which its shareholders are deposit holders and their deposits work as corporation’s equities. The defined bank can perform non-usury operations, and by designing a behavioral model, it is shown that NUBankCo can draw an environment that the welfare of society is to be maximized. Mobility of deposit resources in NUBankCo is less than conventional banks, and there are fewer conflicts between large and small shareholders/depositors and limits the emergence of shareholders’ cartels and thus huge sudden outflow of funds which creates bankruptcy crises.